Convolutional neural network model and software for classification of typical pests - Bezliudnyi, Y.S.; Shymkovysh, V.M.; Doroshenko, A.Yu. (PROBLEMS IN PROGRAMMING, 2022)
A model of a convolutional neural network, a dataset for neural network training, and a software tool for the classification of typical insect pests have been developed, which allows recognizing the class of insect pests from an image. The structure of the neural network model was optimized to improve the classification results. In addition, the user interface, authentication, and authorization, data personalization, the presence of user roles and the appropriate distribution of functionality by role, the ability to view statistics on classified insects in a certain period of time were developed. Functional testing of the developed software application on a heterogeneous set of images of insects of 20 diﬀerent classes was performed.Prombles in programming 2021; 4: 95-102